The Effectiveness of Using Beelinguapp Toward Student's Reading Comprehension - Alifa Nurfalah; Yuyun Bahtiar; Luluk Choirun Nisak; Hanifah Hanifah; A. Kanzul Fikri; Iin Baroroh Ma'arif (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This research was conducted with the aim of knowing the process and the effect of using beelinguapp to reading comprehension ability of 41 students of SMK PGRI Ploso. The research method used was pre-experimental design with the type of one-group pretest-post test design and using a quantitative research approach. The test instrument is in the form of multiple choice questions and essay of pre test and post test descriptions to measure reading comprehension, from the results of the total pre-test scores obtained 1910 while the results of the total post test scores 3235, while the data analysis technique used is hypothesis testing. But before testing the hypothesis, the data obtained was first tested for normality. Based on the results of the data normality test with shapiro-wilk, the pretest results have a significance value of 0.189 and the posttest results have a significance value of 0.191. The normality test is normal. Based on the calculation of the paired sample t-Test it shows that the t value of 0.000 with a significance of 0.000. The significance value shows 0.000 < the error rate of 0.05, so it can be concluded that Ha is accepted. Acceptance of Ha means that there is a positive effect on The Effectiveness of Using Beelinguapp on Reading Comprehension of X Grade Student’s at SMK PGRI Ploso.